Integrasi Generative AI dan Digital Curation dalam Pembelajaran Stoikiometri untuk Meningkatkan Berpikir Kritis dan Gotong Royong Siswa SMA - Gani, Abdul (AS-SABIQUN, 2025)
Stoichiometry is a fundamental topic in high school chemistry education that often leads to misconceptions among students. This study aims to examine the effectiveness of integrating Generative Artificial Intelligence (AI) and digital curation in enhancing students’ understanding of stoichiometric concepts, while also fostering critical thinking skills and the values of gotong royong. A quasi-experimental method with a pretest–posttest control group design was employed, involving 64 Grade XI science students at MA Hidayatussibyan NW Sengkerang. The results indicate that the experimental group experienced a significant improvement in stoichiometric understanding, with an N-Gain score of 0.84, categorized as high. Students' critical thinking skills also showed consistent improvement across multiple assessment tools, including CCTST, CTMS, and CTS. Moreover, collaborative dimensions such as teamwork, collectivism, and the spirit of gotong royong demonstrated significant positive development. Qualitative data further support these findings, highlighting increased active participation in discussions, more equitable role distribution, and stronger peer support. These results suggest that generative AI can reduce misconceptions through adaptive visualizations, while digital curation enhances critical evaluation and culturally grounded collaboration. Overall, this learning model presents an innovative strategy well-suited to address the challenges of 21st-century chemistry education.